Relasi Kuasa Pada Interaksi Sosial Antara Priyayi dan Orang Kebanyakan dalam Novel Gadis Pantai Karya Pramoedya Ananta Toer - Agnibaya, Rangga; Puspitasari, Dhika (Universitas Negeri Padang, 2024)
At the beginning of the 20th century, Javanese society, especially natives, was divided into two distinct social groups, namely nobles or priyayi and Kawula or ‘orang kebanyakan’. These two groups interact in social life in a unique pattern. Both use their respective identities to identify their position in these social relations. This research examines the power relations and identity politics contained in the novel Gadis Pantai by Pramoedya Ananta Toer. By using descriptive qualitative research methods, this research found data that the social relations depicted in the novel Gadis Pantai tend to be unbalanced. This means that there are superior and inferior groups, or there is a master-ruled relationship in this relationship. Priyayi are a superior group, whereas ‘orang kebanyakan’ are an inferior group in terms of social relations. It was also found that priyayi control over ordinary people manifests in several forms: (1) Control in terms of social behavior; (2) Mastering the way of thinking; (3) Mastering the material. This research also examines the forms of strategy in existing power relations.Keywords: priyayi, ‘orang kebanyakan’, power relations